Isolated sarcoid myopathy - Berger, Christian; Sommer, Clemens; Meinck, Hans-Michael (Muscle & nerve, 2002)
A 75-year-old housewife presented with a 5-year history of slowly progressive, painless limb weakness with wasting particularly of the pretibial muscles and without sensory involvement. She was otherwise healthy, but had a history of mild pulmonary sarcoidosis 20 years earlier. Abnormal laboratory findings included serum calcium (3.2 mmol/L; normal 2.15-2.6 mmol/L) and serum angiotensin-converting enzyme (ACE; 38.2 U/L; normal <22.5 U/L). All other laboratory investigations, including antibody studies and diagnostic work-up for systemic sarcoidosis, were negative. Muscle biopsy revealed noncaseating epitheloid granulomas, multinuclear giant cells, and lymphoplasmacellular infiltration. The patient was started on methylprednisolone and recovered to some extent. These findings represent a rare case of isolated sarcoid myopathy without concurrent systemic sarcoidosis. © 2002 Wiley Periodicals, Inc. Muscle Nerve 26: 553-556, 2002